Exclusive Breastfeeding Practices of Mothers in Duakor, a Traditional Migrant Community in Cape Coast, Ghana - Solomon Sika-Bright; Georgina Yaa Oduro (Journal of Global Initiatives, 2013)
Ensuring child health and well-being is critical in Ghana’s development. Central to initia-tives for ensuring child health is the World Health Organization’s (WHO) recommended exclusive breastfeeding, which is increasingly being promoted in Ghana. As the name connotes, the practice requires that babies from age zero to six months are breastfed. This practice is however interpreted and practiced differently in line with the traditional mode of feeding babies in most communities in Ghana. This paper presents the findings of a study that examined how mothers breastfeed their babies in the first six months at Dua-kor, a traditional migrant community in Cape Coast, Ghana. The study involved 48 moth-ers and data was collected through semi-structured interviews. Among others, the study found that friends’ ways of feeding were influential in the way mothers fed their babies. Significantly, traditional feeding habits, such as giving babies water and porridge were found in the migrant community. The study further discovered that an exclusive breast-feeding practice among mothers in Duakor was far from ideal as recommended by the WHO. The study therefore recommends the need for intensive sensitization education and culturally sensitive infant feeding initiatives, taking into consideration traditional homeland feeding practices.